The time course of altered brain activity during 7-day simulated microgravity - Liao, Yang; Lei, Meiying; Huang, Haibo; Wang, Chuang; Duan, Jiaobo; Li, Hongzheng; Liu, Xufeng (Frontiers in Behavioral Neuroscience, 2015)
Microgravity causes multiple changes in physical and mental levels in humans, which can induce performance deficiency among astronauts. Studying the variations in brain activity that occur during microgravity would help astronauts to deal with these changes. In the current study, resting-state functional magnetic resonance imaging (rs-fMRI) was used to observe the variations in brain activity during a 7-day head down tilt (HDT) bed rest, which is a common and reliable model for simulated microgravity. The amplitudes of low frequency fluctuation (ALFF) of twenty subjects were recorded pre-head down tilt (pre-HDT), during a bed rest period (HDT0), and then each day in the HDT period (HDT1–HDT7). One-way analysis of variance of the ALFF values over these 8 days was used to test the variation across time period (P＜0.05, corrected). Compared to HDT0, subjects presented lower ALFF values in the posterior cingulate cortex and higher ALFF values in the anterior cingulate cortex during the HDT period, which may partially account for the lack of cognitive flexibility and alterations in autonomic nervous system seen among astronauts in microgravity. Additionally, the observed improvement in function in CPL during the HDT period may play a compensatory role to the functional decline in the paracentral lobule to sustain normal levels of fine motor control for astronauts in a microgravity environment. Above all, those floating brain activities during 7 days of simulated microgravity may indicate that the brain self-adapts to help astronauts adjust to the multiple negative stressors encountered in a microgravity environment.